Know thy neighbor: Political uncertainty and the informational advantage of local institutional investors - Aabo, Tom; Lee, Suin; Pantzalis, Christos; Park, Jung Chul (Journal of Banking & Finance, 2020)
Previous literature finds a positive association between short-term changes in institutional holdings (especially those of local institutions) and subsequent short-term stock performance. We contribute by investigating the importance of geographical proximity under policy uncertainty. We show that the short-term informational advantage of local institutions only thrives in areas that are either politically closely aligned with the president or where the state government (governorship and legislature) is under the control of one party. Our findings are important in understanding the avenues through which geographical proximity may provide the basis for exploitable informational advantages.